A method for improving the toughness of cycloolefin polymer, a cycloolefin polymer, an optical lens for lens, and an optical lens

By treating the cycloolefin polymer in a high-temperature absorption atmosphere of 150-200°C, a micro-crosslinked structure was formed, which solved the problems of poor toughness and stress cracking, and achieved a significant improvement in the toughness and stability of the material.

CN119735720APending Publication Date: 2025-04-01HANGZHOU RUIFENGRONGCHUANG TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411924306.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

When forming, cycloolefin polymer materials are limited by molecular chain structure, resulting in poor toughness. They are brittle materials and have problems with stress cracking.

Method used

The cyclic olefin polymer is treated in a high-temperature absorption atmosphere of 150-200°C to form a micro-crosslinked structure to improve its toughness.

Benefits of technology

Through high-temperature absorption treatment, the toughness and stability of cycloolefin polymers have been significantly improved, and their resistance to stress cracking has also been improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005208852820000021
    Figure BDA0005208852820000021
  • Figure BDA0005208852820000041
    Figure BDA0005208852820000041
  • Figure BDA0005208852820000061
    Figure BDA0005208852820000061
Patent Text Reader

Abstract

The present invention provides a method for improving the toughness of a cycloolefin polymer, a cycloolefin polymer, an optical lens for a lens, and an optical lens. The method can form a micro-crosslinked structure of the cycloolefin polymer by treating the cycloolefin polymer in an oxygen-free atmosphere at a high temperature of 150 to 200°C, thereby obtaining a glass transition temperature of 110 to 160°C and a maximum value of the first-order derivative of a DSC curve of 0.03 W·g ‑1 ·min ‑1 ~0.50W·g ‑1 ·min ‑1 , a cycloolefin polymer with a molecular weight distribution index of 1.2 to 3.0. The present invention performs injection molding on the cycloolefin polymer after high-temperature anaerobic treatment, and finds that the cracks and cracking degree of the surface are greatly improved, and the rigidity and toughness are well balanced, and the ability to resist stress cracking is also significantly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of optical materials, and specifically relates to a method for improving the toughness of a cycloolefin polymer, a cycloolefin polymer, an optical lens for a lens, and an optical lens. Background Art

[0002] As a thermoplastic optical material, cycloolefin polymer has the characteristics of high transparency, low refractive index, high strength, chemical corrosion resistance and low water absorption. Therefore, it is widely used in optical films and lenses, display screens, polarizers, medical detectors, pharmaceuticals and food packaging.

[0003] At present, cycloolefin polymer materials have poor toughness during molding due to the limitations of their molecular chain structure, and are brittle materials. The resulting products also often have stress cracking problems, resulting in many deficiencies or limitations in polymer processing and application.

[0004] For example, CN 116217806 A discloses a cycloolefin polymer, which can solve the technical problems of the cycloolefin polymer in the prior art that it is difficult to achieve high refractive index, low Abbe number and good mechanical properties, but the problem caused by its own stress cracking has not been alleviated. The prior art generally adopts the introduction of polar cycloolefin monomers to improve the toughness of cycloolefin polymers, but the improvement is not high.

[0005] Therefore, seeking a method to improve the crack resistance of cycloolefin polymers is of great significance for the application of cycloolefin polymers. Summary of the invention

[0006] In view of this, the object of the present invention is to provide a method for improving the toughness of a cycloolefin polymer, a cycloolefin polymer, an optical lens for a lens, and an optical lens. The method can make the cycloolefin polymer have excellent toughness and stability at the same time.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a method for improving the toughness of a cycloolefin polymer, comprising the following steps:

[0009] The cycloolefin polymer is treated at 150-200°C in an oxygen-free atmosphere.

[0010] Preferably, the treatment time is 0.1 to 5 hours.

[0011] Preferably, the structure of the cycloolefin polymer is as shown in Formula I:

[0012]

[0013] Wherein, p is an integer between 1 and 100; n and m are independently 0, 1, 2 or 3;

[0014] R 1 ~R 10 are independently a hydrogen atom, a halogen atom other than a fluorine atom, or an alkyl group having 1 to 10 carbon atoms substituted with a halogen atom other than a fluorine atom;

[0015] or R 3 With R 4 , R 3 With R 9 , R 3 With R 10 and the carbon atoms in which they are located form a ring or a heterocyclic ring;

[0016] or R 5 With R 6 , R 5 With R 7 , R 5 With R 8 and the carbon atoms where they are located form a ring or a heterocycle.

[0017] In a second aspect, the present invention provides a cycloolefin polymer which is processed by the above method.

[0018] Preferably, the glass transition temperature of the cycloolefin polymer is 110-160°C.

[0019] Preferably, the maximum value of the first-order derivative of the DSC curve of the cycloolefin polymer is 0.03 W·g -1 ·min -1 ~0.50W·g -1 ·min -1 .

[0020] Preferably, the molecular weight distribution index of the cycloolefin polymer is 1.2 to 3.0.

[0021] In a third aspect, the present invention provides an optical lens for a lens, which is prepared using the above-mentioned cycloolefin polymer.

[0022] Preferably, the preparation method includes compression molding or injection molding.

[0023] Preferably, the processing temperature of the compression molding or injection molding is 200-300°C.

[0024] In a fourth aspect, the present invention provides an optical lens, which is manufactured by combining the optical lens involved in the above technical solution with other types of optical lenses.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] The present invention provides a method for improving the toughness of a cycloolefin polymer. The method can form a micro-crosslinked structure of the cycloolefin polymer by treating the cycloolefin polymer in an oxygen-free atmosphere at a high temperature of 150 to 200°C, thereby obtaining a glass transition temperature of 110 to 160°C and a maximum value of the first-order derivative of a DSC curve of 0.03 W·g -1 ·min -1 ~0.50W·g -1 ·min -1 , a cycloolefin polymer with a molecular weight distribution index of 1.2 to 3.0. The present invention performs injection molding on the cycloolefin polymer after high-temperature anaerobic treatment, and finds that the cracks and cracking degree of the surface are greatly improved, and the rigidity and toughness are well balanced, and the ability to resist stress cracking is also significantly improved. DETAILED DESCRIPTION

[0027] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] During heat treatment, the molecular chains of cycloolefin polymers are forced to orient, and a large number of benzene rings on the molecular chains make orientation difficult. After molding, the molecular chains forced to orient tend to return to their natural state. After molding, the molecular chains freeze due to the rapid cooling, and the molecular chains cannot be restored to a low potential energy state in time, resulting in high residual internal stress that causes the material to crack, which greatly affects production efficiency and makes the product qualification rate low. However, there are van der Waals forces and mutual entanglement forces between molecular chains inside the material, that is, anti-cracking forces, and their size depends on the length of the molecular chains and the number of entanglements between chains. Based on the above problems, the present invention provides a method for improving the toughness of cycloolefin polymers, comprising the following steps:

[0029] The cycloolefin polymer is treated in an oxygen-free environment at a high temperature of 150 to 200°C.

[0030] It should be noted that the above-mentioned high temperature anaerobic treatment can make the cycloolefin polymer form a micro-crosslinked structure, thereby improving the toughness of the polymer. If the treatment temperature is too low, the micro-crosslinking degree will be insufficient and the desired effect will not be achieved. If it is too high, it will lead to excessive crosslinking, resulting in hardening and brittleness. Therefore, the present invention is preferably treated at 150-200°C, specifically 150°C, 155°C, 160°C, 165°C, 170°C, 175°C, 180°C, 185°C, 190°C, 195°C or 200°C. The treatment time is generally 0.1-5h, such as 0.1h, 0.5h, 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h or 5h.

[0031] The above treatment is carried out under anaerobic conditions to prevent the cycloolefin polymer from being oxidized.

[0032] The present invention has no particular limitation on the structural formula of the cycloolefin polymer. The high-temperature anaerobic treatment method can be applied to cycloolefin polymers of various structures and has universal applicability.

[0033] In some embodiments of the present invention, the structure of the cycloolefin polymer is as shown in Formula I:

[0034]

[0035] Wherein, p is an integer between 1 and 100, such as 1, 10, 20, 30, 40, 50, 60, 70, 80, 90 or 100, etc.; n and m are independently 0, 1, 2 or 3;

[0036] R 1 ~R 10 independently a hydrogen atom, a halogen atom other than a fluorine atom (such as Br, Cl, I), or an alkyl group having 1 to 10 carbon atoms substituted by a halogen atom other than a fluorine atom;

[0037] or R 3 With R 4 , R 3 With R 9 , R 3 With R 10 and the carbon atoms in which they are located form a ring or a heterocyclic ring;

[0038] or R 5 With R 6 , R 5 With R 7 , R 5 With R 8 and the carbon atoms where they are located form a ring or a heterocycle.

[0039] The present invention also provides a cycloolefin polymer obtained by the high-temperature anaerobic treatment.

[0040] The present invention tests the glass transition temperature (i.e., Tg) of the cycloolefin polymer obtained after the high-temperature anaerobic treatment, and finds that the Tg of the cycloolefin polymer is 110-160°C, which is not much different from the cycloolefin polymer not subjected to the high-temperature anaerobic treatment, indicating that the crosslinking degree of the cycloolefin polymer obtained after the high-temperature anaerobic treatment is slightly crosslinked. At the same time, the present invention can also monitor the crosslinking degree of the cycloolefin polymer obtained after the high-temperature anaerobic treatment according to Tg.

[0041] The maximum value of the first derivative of the DSC curve can directly reflect the stress generated by the cycloolefin polymer material during the injection molding process. Generally, if the maximum value of the first derivative of the DSC curve is too high or too low, the polymer material will be more sensitive to temperature. During the molding process, the change in the temperature of the polymer material will cause uneven shrinkage, thus generating stress, which in turn will cause cracking of the molded polymer material. Therefore, it is necessary to ensure that the maximum value of the first derivative of the DSC curve is within an appropriate range.

[0042] According to the test, the maximum value of the first-order derivative of the DSC curve of the cycloolefin polymer after high-temperature anaerobic treatment is 0.03 W·g -1 ·min -1 ~0.50W·g -1 ·min -1 , preferably 0.04 W·g -1 ·min -1 ~0.40W·g -1 ·min -1 , more preferably 0.05 W·g -1 ·min -1 ~0.30W·g -1 ·min -1 Subsequent injection molding processes have found that the surface cracks and collapse of the cycloolefin polymer after high-temperature anaerobic treatment have been greatly improved after injection molding, and the rigidity and toughness have been well balanced, and the ability to resist stress cracking has also been significantly improved.

[0043] The present invention also performs GPC testing on the cycloolefin polymer obtained after high-temperature anaerobic treatment, and finds that its molecular weight distribution index is 1.2-3.0. Compared with the cycloolefin polymer not subjected to high-temperature anaerobic treatment, the molecular weight distribution index does not change much, indicating that high-temperature anaerobic treatment has little effect on the molecular weight distribution index.

[0044] The present invention also provides an optical lens for a lens, which is prepared by using the above-mentioned cycloolefin polymer.

[0045] In the present invention, the preparation method includes compression molding or injection molding. The processing temperature of the compression molding or injection molding is 200-300°C, preferably 240-290°C.

[0046] The present invention also provides an optical lens, which is prepared by combining the optical lens involved in the above technical solution with other types of optical lenses. Here, the other types of optical lenses refer to PMMA lenses (acrylic lenses), PC lenses (polycarbonate lenses), etc.

[0047] In order to further illustrate the present invention, the following examples are provided for detailed description. The experimental raw materials used in the following examples of the present invention are all common commercially available products.

[0048] The DSC test method involved below is: take 3-5 mg of cycloolefin polymer, put it into the instrument and heat it to 240°C at a heating rate of 20°C / min, keep it constant at 240°C for 5 minutes, then cool it to 30°C at a cooling rate of 20°C / min, keep it constant at 30°C for 5 minutes, and finally heat it to 240°C at a heating rate of 20°C / min to end the test. At the same time, the glass transition temperature and the maximum value of the first-order derivative are obtained.

[0049] The GPC test method is as follows: 1 mg of the polymer is dissolved in 1 mL of tetrahydrofuran and the test is performed in an insert detector with a mobile phase speed of 1 mL / min, a column temperature set at 35°C, and a single injection volume of 50 μL.

[0050] Injection stress test: Cycloolefin polymer is injection molded and tested for performance. The injection molding temperature is 240-290°C, and the degree of cracks and collapse on the surface is observed.

[0051] The glass transition temperature ranges from 110°C to 150°C, and the maximum value of the first-order derivative curve of the DSC curve is 0.03 W·g -1 ·min -1 ~0.50W·g -1 ·min -1 .

[0052] Preparation Example 1

[0053] Cycloolefin polymer A was prepared according to the preparation process of Example 1 of patent WO2024127881A1;

[0054] Cycloolefin polymer B was prepared according to the preparation process of Example 2 of patent JP7247704B2;

[0055] Cycloolefin polymer C was prepared according to the preparation process of Example 1 of patent CN117417512A;

[0056] The structural formulas of the above-mentioned cycloolefin polymer A, cycloolefin polymer B and cycloolefin polymer C are as follows:

[0057]

[0058] Examples 1 to 3

[0059] The cycloolefin polymer A obtained in Preparation Example 1 was subjected to high temperature anaerobic treatment, with parameters as shown in Table 1, to obtain cycloolefin polymer A1, which was subjected to DSC test, GPC test and injection stress test. The test results are shown in Table 1.

[0060] Comparative Examples 1 to 3

[0061] The cycloolefin polymer A obtained in Preparation Example 1 was subjected to high temperature anaerobic treatment, with parameters as shown in Table 1, to obtain cycloolefin polymer A1, which was subjected to DSC test, GPC test and injection stress test. The test results are shown in Table 1.

[0062] Comparative Example 4

[0063] The cycloolefin polymer A obtained in Preparation Example 1 was provided as a blank control, and DSC test, GPC test and injection stress test were performed. The test results are shown in Table 1.

[0064] Table 1

[0065]

[0066] Embodiments 4 to 6

[0067] The cycloolefin polymer B obtained in Preparation Example 2 was subjected to high temperature anaerobic treatment, with the parameters detailed in Table 2, to obtain cycloolefin polymer B1, which was subjected to DSC test, GPC test and injection stress test. The test results are shown in Table 2.

[0068] Comparative Examples 5 to 7

[0069] The cycloolefin polymer B obtained in Preparation Example 2 was subjected to high temperature anaerobic treatment, with the parameters detailed in Table 2, to obtain cycloolefin polymer B1, which was subjected to DSC test, GPC test and injection stress test. The test results are shown in Table 2.

[0070] Comparative Example 8

[0071] The cycloolefin polymer B obtained in Preparation Example 2 was provided as a blank control, and DSC test, GPC test and injection stress test were performed. The test results are shown in Table 2.

[0072] Table 2

[0073]

[0074] Embodiments 7 to 9

[0075] The cycloolefin polymer C obtained in Preparation Example 3 was subjected to high temperature anaerobic treatment, and the parameters were detailed in Table 3 to obtain cycloolefin polymer C1, which was subjected to DSC test, GPC test and injection stress test. The test results are shown in Table 3.

[0076] Comparative Examples 9 to 11

[0077] The cycloolefin polymer C obtained in Preparation Example 3 was subjected to high temperature anaerobic treatment, and the parameters were detailed in Table 3 to obtain cycloolefin polymer C1, which was subjected to DSC test, GPC test and injection stress test. The test results are shown in Table 3.

[0078] Comparative Example 12

[0079] The cycloolefin polymer C obtained in Preparation Example 3 was provided as a blank control, and DSC test, GPC test and injection stress test were performed. The test results are shown in Table 3.

[0080] Table 3

[0081]

[0082]

[0083] From the data in Tables 1 to 3, it can be seen that after high-temperature anaerobic treatment at 150 to 200 °C, the glass transition temperature of the cycloolefin polymer can be made to range from 110 to 160 °C, and the maximum value of the first-order derivative curve of the DSC curve is 0.03 W·g -1 ·min -1 ~0.50W·g -1 ·min -1 , the molecular weight distribution index is 1.2 to 3.0, the rigidity and toughness of the cycloolefin polymer are well balanced, and the ability of the cycloolefin polymer to resist stress cracking after injection molding is significantly improved. Therefore, the present invention finds that parameter intervention in the polymerization stage of the cycloolefin polymer to improve the micro-crosslinking of the polymer can effectively improve the stress generated by the subsequent injection molding process, thereby solving the stress cracking problem of the injection molded part.

[0084] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for improving the toughness of a cycloolefin polymer, characterized in that: The following steps are involved: The cycloolefin polymer is treated at 150-200°C in an oxygen-free atmosphere.

2. The method according to claim 1, characterized in that The treatment time is 0.1 to 5 hours.

3. The method according to claim 1 or 2, characterized in that: The structure of the cycloolefin polymer is shown in Formula I: Wherein, p is an integer between 1 and 100; n and m are independently 0, 1, 2 or 3; R1~R 10 are independently a hydrogen atom, a halogen atom other than a fluorine atom, or an alkyl group having 1 to 10 carbon atoms substituted with a halogen atom other than a fluorine atom; Or R3 and R4, R3 and R9, R3 and R 10 and the carbon atoms in which they are located form a ring or a heterocyclic ring; Or R5 and R6, R5 and R7, R5 and R8 and the carbon atoms where they are located form a ring or a heterocycle.

4. A cycloolefin polymer, characterized in that The method according to any one of claims 1 to 3 is used for treatment.

5. The cycloolefin polymer according to claim 4, characterized in that The glass transition temperature of the cycloolefin polymer is 110 to 160° C. The maximum value of the first-order derivative of the DSC curve of the cycloolefin polymer is 0.03 W·g -1 ·min -1 ~0.50W·g -1 ·min -1 .

6. The cycloolefin polymer according to claim 4 or 5, characterized in that The molecular weight distribution index of the cycloolefin polymer is 1.2 to 3.

0.

7. An optical lens for a lens, characterized in that: The method is prepared by using the cycloolefin polymer described in any one of claims 4 to 6.

8. The optical lens for a lens according to claim 7, characterized in that: The preparation method includes compression molding or injection molding.

9. The optical lens for a lens according to claim 8, characterized in that: The processing temperature of the compression molding or injection molding is 200-300°C.

10. An optical lens, characterized in that: The optical lens according to any one of claims 7 to 9 is combined with other types of optical lenses.

Citation Information

Patent Citations

  • Cycloolefin copolymer, optical product, and electronic device

    CN116217806A

  • Cyclic olefin ring-opened polymer hydride, resin composition and film

    WO2024127881A1

Cited By

  • Hydrogenated cycloolefin copolymer, preparation method of hydrogenated cycloolefin copolymer, hydrogenated cycloolefin resin composition and application of hydrogenated cycloolefin resin composition

    CN121717996A